Potensi Daya Tarik Wisata Pada Masjid Al-Hakim Kota Padang - Fasandra, Fernando; Hibatullah, Naufal; Nova, Siska Mitria (Institut Seni Indonesia Padangpanjang, 2023)
Al-Hakim Padang Mosque has the main function as a place of prayer for Muslims, but now it is also being used as a tourist destination. The phenomenon of utilizing the Mosque as a tourist destination needs to be studied so that the Jam'ah of the Mosque who are praying is not disturbed and the Tourism Attraction can be managed. This research aims to identify the Tourism Attraction of Al-Hakim Mosque in Padang City for tourists who have visited. This research uses qualitative methods with conclusions in the form of descriptive results. Data analysis refers to the Miles model with data reduction and narrative data presenting. Data collection was made by using observation, documentation, and interviews with 15 informants with details, 10 tourists, 1 manager of the Al-Hakim Mosque, 1 parking attendant of the Al-Hakim Mosque, 2 local street peddlers around the Al-Hakim Mosque. The results of this study showed that the Padang AlHakim Mosque has a tourist attraction in terms of location, spiritual activities, beach views, facilities, and mosque architecture.